Integrating Gamelan into Problem-Based Learning and Culturally Responsive Teaching-Oriented E-Learning to Enhance Students’ Problem-Solving Skills and Cultural Awareness - Tri Diaz Elvana Rose; Libna Sahlatul Mufidah; Sabar Nurohman; Ismail Fikri Natadiwijaya (Universitas Pendidikan Mandalika, 2026)
This study aims to evaluate the effectiveness of gamelan-integrated e-learning Problem-Based Learning combined with Culturally Responsive Teaching (PBL-CRT) in improving middle school students’ problem-solving skills and cultural awareness. A quantitative pre-experimental approach using a one-group pretest–posttest design was employed, involving 33 eighth-grade students. Data were collected through problem-solving tests and cultural awareness questionnaires administered before and after the intervention. The data were analyzed using nonparametric statistical tests and effect size analysis. The results showed significant improvements in both students’ problem-solving skills and cultural awareness after the implementation of gamelan-integrated e-learning PBL-CRT. The Wilcoxon Signed-Rank Test revealed a significant difference between pretest and posttest scores (Z = −4.937, p = 0.001), while the effect size analysis indicated a very large effect (r = 0.85). Improvements were observed across all indicators of both variables. These findings indicate that gamelan-integrated e-learning PBL-CRT serves as an effective contextual learning approach for enhancing students’ problem-solving skills while fostering greater appreciation and awareness of local culture.